اللغة بين التعلم والاكتساب - عبد بن سلوى, فاطمة (كلية الأدب العربي والفنون, 2024)
تهدف هذه الدراسة إلى معرفة أهمّ التطورات التي شهدها حقل الدراسات اللّغويّة خاصة في مجال تعليم اللّغات، التي تأثر هذا الأخير بعلم اللّسانيّات التي اهتمت باكتساب اللّغة وتعلمها، من خلال ما قدّمته من نظريات، وأهمّ ما جاء به علمائها والنتائج المتوصل إليها من خلال دراساتهم من أجل تطوير هذا المجال، فقد تأثر بهذا العلم الحديث، حيث أسدى إلى البحث اللّغويّ بنظريات أفادت العديد من المجالات خاصة تعليم اللّغة وتعلّمها his study aims to know the most important developments that the field of linguistic studies has witnessed, especially in the field of language teaching, which was influenced by the science of linguistics, which was concerned with language acquisition and learning, through the theories it presented, the most important findings of its scholars and the results reached through their studies in order to The development of this field was influenced by modern science, as it led to linguistic research with theories that benefited many fields, especially language teaching and learning
Keywords: اللّسانيّات، اكتساب اللّغة، النظريات اللّسانيّة، العملية التعليمية.; linguistics, language acquisition, linguistic theories, educational process.